UK air transport policy in the context of Europe Thursday 1 June 2000 - Soames, T. (Thomas Telford, 2000)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Speakers' notes for a conference held on 1 June 2000.
Keywords: Aeronautics, Commercial -- Government policy -- Great Britain -- Congresses.; Aeronautics, Commercial -- Europe -- Congresses.; elektronické knihy; electronic books